HUBUNGAN DUKUNGAN KELUARGA DENGAN PSYCHOLOGICAL WELL BEING PADA PASIEN STROKE - Widuri, Sri; MIRASARI, TRIANA; Kusdhiarningsih, Betty (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2025)
Stroke is the second leading cause of death globally and the third leading cause of disability. After a stroke, a person may experience psychological disorders, which occur due to emotional disturbances, pain, sleep disturbances, depression, dysphagia, and can lead to death in patients, resulting in low psychological well-being. Family support is a crucial element in the healing and recovery process of a disease. The purpose of this study was to determine the relationship between family support and psychological well-being in stroke patients. This study used a correlational analytical method with a cross-sectional approach. The location of this study was the inpatient ward of RSI Amal Sehat Sragen. The sample used was 34 patients, with the sampling technique being asidental sampling. Data analysis used a spearhead test to determine the relationship between family support and psychological well-being in stroke patients. The p-value in both groups was 0.000, which is less than 0.05, indicating a relationship between family support and psychological well-being in stroke patients.